Research of stress-deformed state of main gas-pipeline section in loose soil settlement; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development 7–11 April 2014, Tomsk, Russia - Burkov P. V. Petr Vladimirovich; Kalmykova K.; Burkova S. P. Svetlana Petrovna; Do Thi Thu Tien (Modern Technologies of Oil and Gas Pipelines and Storage Tanks. Process Simulation of Oil and Gas Transportation, 2014)
Title screen